The Red Pirogue: A Tale of Adventure in the Canadian Wilds - Roberts, Theodore Goodridge, 1877-1953; Merrill, Frank T., 1848-1923 (Salt Lake City, UT : Project Gutenberg, 2020)
"The Red Pirogue: A Tale of Adventure in the Canadian Wilds" by Captain Theodore Goodridge Roberts is a fiction novel likely written in the early 20th century. This tale revolves around young Ben O'Dell, who unexpectedly encounters a little girl named Marion Sherwood while tending to salmon nets, which unfolds a series of mysterious and adventurous events intertwined with her father, a fugitive, and the enigmatic past involving their family. The opening of the novel introduces us to Ben O'Dell, an eighteen-year-old who, while navigating the beautiful Canadian wilds, discovers a large red pirogue and its occupant, a young girl named Marion. Their interaction reveals that her father, Richard Sherwood, is on the run, entangled in past troubles related to the Balenger family. As Ben helps Marion to his home, the story hints at deeper layers of conflict involving Sherwood's past and the peculiar circumstances surrounding their lives, including the burning of the red pirogue and the unexplained thefts at O'Dell's Point. This intriguing setup captures the reader's attention, creating a sense of adventure and suspense that promises further exploration of the characters$1 (Bfates and the mysteries of the wilds they inhabit. (This is an automatically generated summary.)s
Release date is 2020-07-27
Roger Frank and the Online Distributed Proofreading Team
Keywords: Adventure stories; Canada -- Juvenile fiction; Mystery fiction; Fugitives from justice -- Juvenile fiction; Frontier and pioneer life -- Ontario -- Juvenile fiction; Murder -- Investigation -- Juvenile fiction